DISCOVERY OF PHOTOCYTOTOXIC CHLOROPHYLL DERIVATIVES FROM ANTARCTIC, ARCTIC, AND TROPICAL CHLORELLA - KAI-HUEY WONG; KWOK-WEN NG; BOON-SENG TAN; YEN-PING NG; JING NG (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of the study is to investigate tropical and polar Chlorella strains as natural sources of photosensitizers and determine how environmental adaptation to extreme habitats influences photocytotoxic metabolite production for photodynamic therapy (PDT). Methods: Four Chlorella strains, tropical (TRP), Antarctic (ANS and ANT), and Arctic (ARC) were cultured under controlled laboratory conditions for 10 and 15 days. Methanolic and butanolic extracts were screened for photocytotoxicity against HL60 leukemia cells using an MTT assay under broad-spectrum light irradiation. Active extracts were dereplicated by ultra-performance liquid chromatography-photodiode array-mass spectrometry (UPLC-PDA-MS) and high-resolution mass spectrometry (HRMS)/MS to identify known and novel photosensitizers. Results: Of the 16 extracts tested, only day-15 methanolic extracts showed strong light-dependent cytotoxicity. TRP and ANT reduced HL60 viability by more than two-fold upon irradiation compared to dark controls. Metabolomic profiling identified nine known chlorophyll-derived photosensitizers and revealed three previously unreported chlorophyll-based compounds (m/z 623, 531, 663) with distinct Soret and Q-band absorptions. The tropical strain TRP, adapted to high irradiance and thermal stress, yielded the highest diversity and abundance of photosensitizers. In contrast, polar strains produced lower levels, possibly reflecting culture conditions that did not replicate their native extreme light regimens. Conclusion: This study highlights Chlorella as a sustainable reservoir of photosensitizers and shows that adaptation to extreme environments shapes their biosynthetic potential. The discovery of three novel chlorophyll derivatives expands the repertoire of natural photosensitizers and underscores the promise of microalgae as biofactories for next-generation PDT agents.